PEDAGOGICAL FOUNDATIONS OF THE USE OF AN INTEGRATIVE APPROACH AND INTERDISCIPLINARY CONNECTION IN THE EDUCATIONAL PROCESS (Intent Research Scientific Journal, 2023)
Integration in education is the establishment of connections between the components of the content within a certain educational system in order to form a holistic view of the world aimed at the development of the learner's personality and self-development process. Integration is a process that teaches systematization and simplification of complexity in education.